PENGEMBANGAN PARIWISATA SEBAGAI UPAYA PENGENTASAN KEMISKINAN DI SEKITAR PANTAI KARTINI, KABUPATEN JEPARA - Mega Sesotyaningtyas; Wiwik Dwi Pratiwi (Diponegoro University, 2018)
Poverty is a complex issue that gained significant attention in Indonesia. Various strategies and programs have been carried out by the government to solve the poverty issue. However, the result is not satisfactory. One of the endeavors which conducted by the government is by initiating tourism sector to encourage the improvement of people welfare by means of good services and tourism businesses provision. This paper aims to describe the role of tourism development in improving dwelling infrastructure and providing tourism facilities, in the effort to alleviate poverty in Pantai Kartini. Examines 120 dwellings is located close to Pantai Kartini (as Zone A) and quite far from Pantai Kartini (as Zone B). This shows that tourism development in Pantai Kartini gives enough impact in reducing the number of poor people. The differences of both dwelling areas around Pantai Kartini are caused by the intensity of connectivity and easiness access between the dwelling area and the tourism area.